Quality evaluation of paper based dental records keeping at a teaching hospital in a developing country (2014)
Introduction: The quality of dental records keeping is instrumental to the improvement of Service delivery, thus adequacy of the records can guide quality assurance. The study evaluated the quality of dental records keeping by dentists at a single hospital in a developing country. Materials: This was a retrospective review of the charts of patients seen at the Dental Out-patients Clinic of the University College Hospital, Ibadan over a six month period. The charts were reviewed for completeness of entries, Status of the dentist as an intern or post registration dentist and Statistical analysis performed using SPSS Software. Results: A total of 1060 charts were reviewed of which none contained all the necessary Information. The most complete Information was the Identification data (99.4%) and the most incomplete was informed consent (100%). Post registration dentists were more likely than interns to make complete documentations of medication history (p = 0.038), clinical findings (p = 0.003), treatment plan (0.048) and medications administered (0.002). Conclusions: There is a fair degree of adequacy of dental records keeping in the tertiary hospital studied in Ibadan, Nigeria. However, suboptimal recordings were noted in areas involving explanations by the dentist to the patient